Prospects for trade unions and labour organisations in India's IT and ITES industries. (1st October 2010) - Andrew Stevens; Vincent Mosco
Abstract : Drawing on interviews conducted with trade unionists and labour activists in 2008, this article addresses nascent unions and professional associations operating in India's information technology (IT) and IT-enabled services (ITES) industries. This work builds upon the literature that is developing around unionisation within knowledge- and information-based workplaces, and is particularly informed by the work of Mosco and McKercher (Mosco & McKercher, 2008; McKercher & Mosco, 2006, 2007), whose research focuses on knowledge worker mobilisation. Such an approach, as adopted here, requires reflection on India's industrial relations regime and the IT and ITES industries' political-economic framework in the broader context of the new international division of labour, based on the increasingly fragmented commodity production chains that are distributed throughout the globe. The central theoretical model is grounded on a critical political economy of communication (Mosco, 2009).